TORQUE AND SQUARE-ROOT-FUNCTION - Kepp, Peter (European Scientific Journal, ESJ, 2013)
• A new view on the root-function. • Numbers used in their particular, mathematical function – as the value of a measure in a unit. • By example, a view on that multiplications (genuine multiplication) which produce new units. • The way to understand why the square-root of a negative radicand is solvable by an operational way and why we have to define the root-function new. • Altogether the first step of a restructuring of whole the numerical mathematics – a reform of the signs